Management of time and cost contingencies in construction projects: a contractor perspective - Ortiz, José I.; Pellicer, Eugenio; Molenaar, Keith R. (Journal of Civil Engineering and Management, 2018)
The management of threats and opportunities plays a key-role in enhancing project performance. However, there is a gap in literature concerning how general contractors manage threats and opportunities in construction projects, in particular in the use of time and cost contingencies. This research partially addresses this gap through a case study of two large Spanish construction companies. The research presented two key factors determining how the contractors analyzed manage time and cost contingencies: project objectives and existing mistrust among the contractor’s team members. The research also found that managers use time and cost contingencies not only to manage threats, but also as tools for managing opportunities, thereby providing insight into a previously undescribed form of contingency: the negative contingency. The research results enable a better understanding of the actual behavior of general contractors, which contributes to paving the way for developing enhanced methods for contingencies management.